Altered serum cytokines in patients with symptomatic disk herniation and depressive symptoms - Bielewicz, Joanna; Daniluk, Beata; Kamieniak, Piotr (Frontiers in Neuroscience, 2024)
An increasing number of studies have indicated the important role of cytokines in the development of depressive disturbances (DD). In medically ill patients, cytokines can provoked sickness behavior, the signs of which resemble DD. This results in alterations in behavior to limit energy expenditure and redirect it to cope with particular diseases. The aim of our study was to investigate the role of pro-inflammatory IL-6, TNF-α, and IL-1β and anti-inflammatory IL-10 and TGF-β in DD observed in patients suffering from pain caused by disc herniation (DH) qualified for surgery.The intensity of DD assessed by using Beck Depression Inventory, pain intensity, and functional impairment were evaluated in 70 patients with DH who were qualified for surgery. Pro-inflammatory serum levels of TNF-α, IL-1, IL-6, anti-inflammatory TGF-β, and IL-10 were measured.Elevated serum levels of TGF-β, IL-10, and IL-6 were found in the group with moderate and severe depressive symptoms (SD) compared with the groups with mild (MD) or no depressive symptoms (ND). TGF-β levels were negatively correlated with pain intensity, as assessed using the Present Pain Intensity scale in SD. Functional impairment measured using the Oswestry Disability Index was the most advanced in SD group.Results of our study can suggest association between depressive disturbances and antiinflammatory cytokines TGF-β and IL-10. Functional impairment of SD group is more severe but serum levels of TGF-β and IL-10, which are involved in the healing processes, are increased.